2015
DOI: 10.1039/c5py00303b
|View full text |Cite
|
Sign up to set email alerts
|

Group 4 metal complexes bearing the aminoborane motif: origin of tandem ring-opening metathesis/vinyl-insertion polymerization

Abstract: ARTICLE This journal isThree tailored ansa-type Zr (IV)-and Hf (IV)-complexes, Zr-1, Hf-1 and Zr-2, all bridged by a dimethylsilylene group and bearing both a 6-[2-(BR2)phenyl]pyrid-2-yl motif (R = ethyl, mesityl) and an η 1 /η 5 -bound ligand with different Lewis base character and steric demand, have been synthesized. Their structures have been determined by single-crystal X-ray diffraction analysis. Upon activation with methylalumoxane (MAO), Zr-1, Hf-1 and Zr-2 are capable of polymerizing norborn-2-ene (NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In these both complexes, one THF molecule is coordinated to the respective metal center affording pentagonal bipyramidal geometry to the respective complex. In the previously reported other similar complexes, the fluorenyl moiety is coordinated with the metal center in an g 5 -coordination mode, but it is coordinated in an g 1 -coordination in the present examples [102]. The g 1 -coordination instead of g 5 -coordination is probably due to the coordination of other donor groups prior to fluorenyl group coordination and such a bonding mode provides less electron density to electrophilic Zr atom which thus makes a compensation of electron density from pyridine ring and hence reducing electron density on pyridine nitrogen which makes pyridine nitrogen unable to coordinate with B atom.…”
Section: Hafnium Aminopyridinate-f1 Hybrid Catalystsmentioning
confidence: 39%
See 2 more Smart Citations
“…In these both complexes, one THF molecule is coordinated to the respective metal center affording pentagonal bipyramidal geometry to the respective complex. In the previously reported other similar complexes, the fluorenyl moiety is coordinated with the metal center in an g 5 -coordination mode, but it is coordinated in an g 1 -coordination in the present examples [102]. The g 1 -coordination instead of g 5 -coordination is probably due to the coordination of other donor groups prior to fluorenyl group coordination and such a bonding mode provides less electron density to electrophilic Zr atom which thus makes a compensation of electron density from pyridine ring and hence reducing electron density on pyridine nitrogen which makes pyridine nitrogen unable to coordinate with B atom.…”
Section: Hafnium Aminopyridinate-f1 Hybrid Catalystsmentioning
confidence: 39%
“…Catalyst system 74/MAO was also applied for copolymerization of NBE with ethylene and found that the activity of catalyst decreases with increasing concentration of NBE; however, this effect was counter-balanced with increasing ethylene concentration. 13 C-NMR of copolymers is indicative of both alternating and isolated monomer sequences (Table 4) [102]. These copolymers did not show ROMP-derived poly(NBE); however, copolymer obtained from 81/MAO VIP-derived poly(NBE) was observed but the catalyst system 81/MAO was found less active than 74/ MAO.…”
Section: Hafnium Aminopyridinate-f1 Hybrid Catalystsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, this would proceed via a four‐membered transition state, and none of the terminal vinyl groups that would result from such a pathway were observed by using NMR spectroscopy. The high cis content of the resulting polymers is typical for Cp*‐containing metal complexes and is a direct consequence of the substantial steric demand of the Cp* ligand: it forces the NBE to add predominantly anti to the growing polymer chain, which thereby forms a cis double bond (see inset in Scheme , structure A). From the 13 C NMR spectra, a syndiotactic ( st ) polymer structure can be deduced unambiguously (Figure S46).…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, this effectively suppresses β‐hydride‐elimination, as suggested by the high molecular weights of the E‐NBE copolymers with M n >6×10 6 g mol −1 . On the other hand, it also suppresses NBE coordination to a cationic Ti−NBE−(E) n species, that is, to a catalytic species the last inserted monomer of which was NBE, which has been proposed to be a crucial step for α‐H + ‐elimination and the formation of ROMP‐active species . The 13 C NMR spectrum of poly( E )‐ co ‐poly(NBE) suggests the existence of larger PE blocks interrupted by alt ‐ st ‐E‐NBE or isolated −(E‐E n ‐E‐NBE‐E‐E n ‐E)− sequences ( n= 0 or 1; Figure ).…”
Section: Resultsmentioning
confidence: 99%